The Effect of Training on Employee Productivity at PT Atrust Mitra Usaha Indonesia Ice Tea Division Jabodetabek - Zaenuri, Muhamad; Irawan, Pristanto Ria; Rahman, Erik; Fa’uzobihi, Fa’uzobihi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The purpose of this research is to determine the effect of training on employee work productivity at PT. Atrust Mitra UsahaIndonesian Ice Tea Division Jabodetabek This research uses quantitative descriptive methods with data collection techniques through distributing questionnaires and library data. This research uses the method saturated sampling which are used in total 74 employees at PT. Atrust Mitra Usaha Indonesian Ice Tea Division Jabodetabek, using simple linear regression data analysis techniques. The results of this research show that there is an influence between training and performance work productivity positive influence strong and has an influential contribution of 68,2% on work productivity variables. It is hoped that the results of this research will contribute to further research.